Pengaruh Perubahan Tata Guna Lahan Terhadap Peningkatan Limpasan Permukaan Akibat Urbanisasi Dan Risiko Banjir - Harefa, Yosua Ifanemaga (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
Land use change due to urbanization has a significant impact on increasing surface runoff and flood risk in urban areas. This study aims to analyze the effect of converting agricultural and natural vegetation areas into residential and industrial zones on surface runoff and flood potential. Data were collected through satellite image analysis, field surveys, and historical rainfall and river discharge records. The analysis was conducted using the Curve Number (CN) method to calculate surface runoff and Pearson correlation to examine the significant relationship between land use change and peak discharge. The results show that urbanization increased impervious surface area by up to 32%, resulting in an average runoff increase of 48.6%. Pearson correlation analysis indicates a very strong relationship between land use change and peak discharge (r = 0.82, p < 0.01). Flood risk mapping indicates that urban centers and suburban areas with high urbanization levels face the highest flood risk. The study recommends sustainable land use management through conservation of infiltration areas, development of natural drainage systems, and regulation of green open spaces to mitigate flood risks.